Impacts of Green HRM Practices in Employee Environmental Commitment in the Context of Nepalese Manufacturing Industry - Rijal, Rheet (Journal of Innovation in Academia, 2023)
The purpose of this study is to identify various green Human Resource Management (HRM) practices applied in the Nepalese manufacturing industry that contribute to employee environmental commitment. The study adopts a deductive approach grounded in a positivist perspective, utilizing a quantitative approach to collect and analyze data through structured survey questionnaires. The sample size for this study is 446. The researcher collected primary data from employees working in the Nepalese manufacturing industry that has implemented Green HRM practices, using a self-administered questionnaire. The initial data was subsequently analyzed using various statistical techniques, including percentages, frequency analysis, calculating the mean and standard deviation. Additionally, structural equation modeling was employed for inferential analysis. Based on the results of the structural equation model, it was found that green training, green rewards, and organizational culture significantly contribute to employee environmental commitment. The findings of this study emphasize the importance of organizations prioritizing and investing in sustainable HR practices, such as green training, green rewards, and organizational commitment strategies. By doing so, organizations can enhance their commitment to environmental sustainability and ultimately improve their long-term organizational performance.